(untitled) - Langan, John (Boston, MA., 2003)
This quick and and practical guide to grammar, punctuation, and usage skills contains important features that distinguish it from other grammar workbooks. The text's three-part format highlights the 16 most vital grammar skills up front, leaving the rest of the text for secondary topics and additional grammar activities. A self-teaching approach enables students to see exactly what they need to brush up on, and gives them focused examples and practice exercises to speed them to mastery. Finally, the manageable size and short, well-organized chapters give students just the coverage they need.
Keywords: English language,English language; Rhetoric,Problems, exercises, etc.,Grammar,Problems, exercises, etc